Growth and Yield Performance of Pleurotus Florida (Oyster Mushroom) On Different Agriculture Substrates (International Journal of Scientific Research in Science and Technology, 2024)
Mushrooms are one of the most loved foods not only for its exotic taste but also for the benefits with which it comes. They are low in salt and sugar and are a rich natural source of Vitamin D. They contain 25-50% proteins on dry weight basis. The percentage of proteins in mushrooms is much higher than in cereals, pulses, fruits or vegetables. The proteins of mushrooms contain all essential amino acids and their quantity is higher than in the egg. Pleurotus florida (Oyster Mushrooms) are saprophytic fungi that are macro edible mushroom. It may be cultivated on a variety of substrates with acceptable food quality and quantity. The present study was carried out using the different agricultural substrate (Wheat straw, Bajra, Soyabean, Pigeon pea, Chickpea, Sugarcane Maize and Moong) to evaluate the effect of different agriculture substrate on growth of Mycelium, Yield and Biological Efficiency of Pleurotus florida (Oyster mushroom). The yield and Biological Efficiency for Pleurotus florida (Oyster mushroom) on different agriculture substrates was compared. Soyabean substrate was found to be a potential substrate for cultivation of Pleurotus florida (Oyster mushroom). Biological Efficiency on Soyabean 50% while Chickpea- 45%, Pigeon pea- 36%, Moong- 35%, Bajra- 30% Wheat Straw- 25%, Maize- 17% and Sugarcane- 15%. Pleurotus florida (Oyster mushroom) yielded better on substrate Soyabean – 500g. Hence it was concluded that Soyabean gives higher yield as compared to Chickpea, Pigeon pea, Moong, Bajra, Wheat Straw, Maize and Sugarcane substrate.